Elbow heterotopic ossification after distal biceps tendon repair presenting as median nerve neuropathy: A case report. (June 2022) - Daskalakis, Ioannis; Sperelakis, Ioannis; Tosounidis, Theodoros H.; Galanakis, Ioannis
Abstract: Ruptures of the distal attachment of the biceps brachii are rare injuries that typically occur in the dominant arm of men between the third and fourth decade of life. Surgical repair is indicated in active patients. Complications of surgical repair include neurovascular injury, heterotopic ossification, wound infection, elbow stiffness and re-rupture. Heterotopic ossification of the elbow is a rare complication of distal biceps tendon repair operations. It may be entirely asymptomatic or present with symptoms and signs such as swelling, erythema, pain, palpable mass, vascular and nerve compression or joint movement restriction. We present a case of heterotopic ossification presenting as median nerve neuropathy after distal biceps tendon repair using a limited volar single incision.